Meningkatkan Prestasi Belajar Menggunakan Metode Demonstrasi pada Materi Wudhu Kelas II SDN 04 Siparayo - Asneli Asneli; Anggi Sari Putri (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to determine whether the demonstration method can improve student learning achievement in wudhu material among second-grade students at SDN 04 Siparayo in the 2022/2023 academic year. This classroom action research uses the demonstration method. This study is a classroom action research with three cycles through four stages, namely planning, implementation, observation, and reflection. The subjects of this study were 32 students. The hypothesis proposed is that if the demonstration method is used properly, it can improve the learning achievement of students in Islamic Education subjects in grade II of SDN 04 Siparayo in the 2022/2023 academic year. The success indicator is 75% with a minimum passing grade of 75. The data collection technique is observation. The data analysis technique uses a formula to determine the average score and percentage. The results showed that learning achievement in cycle I was 44% or 14 students with a minimum passing grade of 75, cycle II was 56% or 18 students with a minimum passing grade of 75, and cycle III was 81% or 26 students for the material on the pillars of wudu and 87.5% or 28 students for the material on the sunnah of wudu with a minimum passing grade of 75. The increase in student learning achievement from cycle I to cycle II was 12% with a minimum passing grade of 75, while the increase in achievement from cycle II to cycle III was 25% for the material on the pillars of wudhu and 31.5% for the material on the sunnah of wudhu.